Luminal and cytosolic pH feedback on proton pump activity and ATPaAffinity of V-type ATPase from Arabidopsis - Rienmüller, Florian Christian; Schumacher, Karin (The journal of biological chemistry, 2012)
Proton pumping of the vacuolar-type H+-ATPase into the lumen of the central plant organelle generates a proton gradient of often 1-2 pH units or more. Although structural aspects of the V-type ATPase have been studied in great detail, the question of whether and how the proton pump action is controlled by the proton concentration on both sides of the membrane is not understood. Applying the patch clamp technique to isolated vacuoles from Arabidopsis mesophyll cells in the whole-vacuole mode, we studied the response of the V-ATPase to protons, voltage, and ATP. Current-voltage relationships at different luminal pH values indicated decreasing coupling ratios with acidification. A detailed study of ATP-dependent H+-pump currents at a variety of different pH conditions showed a complex regulation of V-ATPase activity by both cytosolic and vacuolar pH. At cytosolic pH 7.5, vacuolar pH changes had relative little effects. Yet, at cytosolic pH 5.5, a 100-fold increase in vacuolar proton concentration resulted in a 70-fold increase of the affinity for ATP binding on the cytosolic side. Changes in pH on either side of the membrane seem to be transferred by the V-ATPase to the other side. A mathematical model was developed that indicates a feedback of proton concentration on peak H+ current amplitude (vmax) and ATP consumption (Km) of the V-ATPase. It proposes that for efficient V-ATPase function dissociation of transported protons from the pump protein might become higher with increasing pH. This feature results in an optimization of H+ pumping by the V-ATPase according to existing H+ concentrations.